Effect of immunostimulatory feed supplements on the development of acquired immunity in rainbow trout (Oncorhynchus mykiss). Issue 86 (March 2019) - Menanteau-Ledouble, Simon; van Sorgen, Frouke; Gonçalves, Rui Alexandre; El-Matbouli, Mansour
Abstract: Immunostimulatory feed supplements are an increasingly common feature of aquaculture management and their benefit has been confirmed for a wide area of products. However, these investigations have often focused on the benefit of these supplements on the innate immune system. In the current project, we investigated a mixture of two commercial feed supplements (Biotronic ® Top 3 and Levabon ® Aquagrow E) with a known protective effect against bacterial infections. The effect of the supplemented diet on antibody titters of Oncorhynchus mykiss vaccinated against Yersinia ruckeri was determined by ELISA. Furthermore, an infection trial was performed to confirm the effect of the supplements on the survival of the fish. Finally, their effects on the growth parameters of the fish were also determined. The results from this study found no significant effect on the general antibody titters. However, when considering only the titters of specific anti- Y ruckeri antibodies, the supplemented feed was associated with an improved response to the vaccine, significantly better than in the fish that had received the control feed. Highlights: We investigated the effect of immunostimulatory supplements in Oncorhynchus mykiss . We used a combination of two commercially available supplement. Vaccination was performed using a commercial vaccine against Yersinia ruckeri . The supplemented diet resulted higher antibody titters following vaccination.